Building Awareness of Islamic Education: A Case Study in Wiyurejo Village, Pujon District, Malang Regency - Noer Hidayah; Lulu'atul Mudrikah (Didaktika Religia, 2020)
Education is the process of preparing the future of students in achieving life goals to have better quality. Education itself has an important role in human life. As Islamic as a religion that is rahmatan lil 'alamin gives serious attention to the development of education for human survival. The importance of Islamic education makes the author interested in finding solutions to build public awareness of the importance of Islamic education. Here the community is classified as minimally educated; many children do not continue their education, which in turn creates social disparities in their lives. Researchers use a phenomenological method, which is from phenomenology. Wherefrom the existing phenomena the writer tries to find out the reasons, causes, and preventive actions that must be taken in the future. From the study, it was found that 14 out of 19 children aged 14-17 did not attend school. 22 out of 22 children aged 7-12 are attending school and 6 out of 6 children aged 12-14 are attending school. The reasons for not going to school are 1) children are not interested in learning, 2) economic factors, 3) wrong associations. Preventive actions that must be taken are modeling and da'wah.